A sporadic diffuse multiple cutaneous leiomyomatosis mimicking plexiform neurofibromatosis: A surgical challenge - Gajanand M. Antakanavar; Bijaylaxmi Sahoo; Aneet Kaur; Ishu Ghiloria; Ajay Jangid; Bhavishya Shetty (Wiley, 2024)
Abstract A 32‐year‐old male presented with diffuse plaques accompanied by multiple large, painful swellings predominantly distributed over the trunk, face and both upper and lower extremities for 11 years. There was no family history of similar complaints. The histopathological examination (HPE), supplemented with special stains confirmed the diagnosis of cutaneous leiomyoma (CL). The immunohistochemical analysis showed a strong expression of smooth muscle actin. The final diagnosis of sporadic diffuse multiple cutaneous leiomyomatosis was made. This presentation of CL is uncommon and resembled plexiform neurofibroma. The clinical diagnosis of this presentation was challenging. Therefore, HPE combined with special stains aided in confirming this surgically challenging rare tumour. In resource‐poor settings regular screening is required for early detection of renal cancer and other associated complications.